AB0431 Clinical Evaluation of Treat-to-Target Strategy-Based Management Using Shortening Interval Methods for Infliximab in Patients with Rheumatoid Arthritis. (9th June 2015) - Kurasawa, T.; Suzuki, K.; Hanaoka, H.; Kaneko, Y.; Yasuoka, H.; Seta, N.; Yamaoka, K.; Kameda, H.; Takeuchi, T.
Abstract : Background: Treat-to-target (T2T) is a strategic approach to achieving remission or at least better control of disease activity, and is recommended in the clinical treatment of rheumatoid arthritis (RA). 1) In Japan, use of increased doses of infliximab (IFX) (up to 10mg/kg) or shortening of dosing interval (minimum every 4 weeks) has been approved since July 2009. Although the efficacy of increased doses of IFX has been reported 2, 3), the efficacy and safety of shortening dosing intervals in T2T-based practice has not been clinically evaluated, despite its importance. Objectives: To clarify the efficacy and safety of T2T strategy-based management with shortened intervals of IFX for RA. Methods: Among 496 consecutive RA patients treated with IFX from August 2009 to December 2014, 124 patients were treated by T2T-based management by shortening intervals (six weeks or less) of IFX. Observation period was 12 months. Efficacy and safety were retrospectively and statistically evaluated using clinical information. Results: In the shortening interval group, 83% were female. Mean age was 55 years, and mean disease duration was 88 months at IFX start. Average SDAI and concomitant methotrexate dose was 27.5 and 8.5 mg/week. During observation, interval was adjusted in 39.5% of patients whereas both interval and dose were adjusted in 61.5%. At 12 months, continuation rate after shortening of IFX was 63.7% and significant improvement in SDAI and HAQ-DI was confirmed (Figure 1 ). 44.2% of patients achieved remission, and disease activity was less than low in 86.6% in the SDAI category. In the shortening interval group without increased doses of IFX, continuation rate was 53.1% and 65.0% of patients achieved remission at 12 months. In contrast, the main causes of discontinuation were insufficient efficacy in 25 cases and adverse events in 9, including infusion reaction (5), pneumonia (3), and malignancy (1) in the shortening interval group. Conclusions: Our consecutive cohort analysis concluded that T2T-based management by shortening intervals of IFX for active RA showed good efficacy and a good overall safety profile in clinical practice. This strategy is considered to be a useful option for the earlier achievement of remission. References: Smolen JS et.al. Ann Rheum Dis. 2010;69(4):631-7. Takeuchi T et.al. Mod Rheumatol. 2009;19(5):478-87. Takeuchi T et.al. Ann Rheum Dis. 2012;71(9):1583-5. Disclosure of Interest: T. Kurasawa: None declared, K. Suzuki Grant/research support from: Eisai Co.Ltd. and Bristol-Myers Squibb Company, H. Hanaoka Consultant for: Astrazeneca, Y. Kaneko Consultant for: Abbvie, Paid instructor for: Eisai Pharmaceutical, Chugai Pharmaceutical, Astellas Pharmaceutical, Mitsubishi Tanabe Pharma Corporation, Pfizer, Speakers bureau: Abbvie, Eisai Pharmaceutical, Chugai Pharmaceutical, Bristol Myers Squibb, Astellas Pharmaceutical, Mitsubishi Tanabe Pharma Corporation, Pfizer, Janssen, UCB, H. Yasuoka Consultant for: Abbvie, N. Seta: None declared, K. Yamaoka Consultant for: Pfizer, Speakers bureau: Pfizer, Chugai Pharma, Mitsubishi-Tanabe Pharma, Takeda Industrial Pharma, GlaxoSmithKline, Nippon Shinyaku, Eli Lilly, Janssen Pharma, Eisai Pharma, Astellas Pharma and Actelion Pharmaceuticals, H. Kameda Grant/research support from: Mitsubishi Tanabe Pharma Corporation, Takeda Pharmaceutical Company, Speakers bureau: Mitsubishi Tanabe Pharma Corporation, T. Takeuchi Grant/research support from: Astellas Pharma, Bristol–Myers K.K., Chugai Pharmaceutical Co, Ltd., Daiichi Sankyo Co., Ltd., Eisai Co., Ltd., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., Santen Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co., Ltd., Teijin Pharma Ltd., AbbVie GK, Asahikasei Pharma Corp., and Taisho Toyama Pharmaceutical Co., Ltd., SymBio Pharmaceuticals Ltd., Consultant for: Astra Zeneca K.K., Eli Lilly Japan K.K., Novartis Pharma K.K., Mitsubishi Tanabe Pharma Co., and Asahi Kasei Medical K.K., abbivie GK, Daiichi Sankyo Co., Ltd., Bristol–Myers K.K., Nipponkayaku Co.Ltd., Paid instructor for: Mitsubishi Tanabe Pharma Co., Eisai Co., Ltd., Abbivie GK, Speakers bureau: AbbVie GK., Bristol–Myers K.K., Chugai Pharmaceutical Co, . Ltd., Eisai Co., Ltd., Janssen Pharmaceutical K.K., Mitsubishi Tanabe Pharma Co., Pfizer Japan Inc., and Takeda Pharmaceutical Co., Ltd., Astellas Pharma, and Diaichi Sankyo Co., Ltd., Celtrion, Nipponkayaku Co.Ltd